Analisis faktor kesulitan membaca permulaan pada peserta didik kelas II sekolah dasar - Prisna Dwi Herfiani; Peduk Rintayati; Fadhil Purnama Adi (Didaktika Dwija Indria, 2023)
The purpose of this study are 1) to identify early reading difficulties factors in SDN 2 Sumberingin and 2) the ways to overcome early reading difficulties. This research is using qualitative research with a case study approach. The subject in this research is 2nd-grade students. Data collection techniques using tests, observation, and interviews. Based on data from this research, the results show that 4 students still have reading difficulties. The difficulties such as identifying letters, having errors in pronouncing sentences, unfluent reading, and wrong intonation. The error are caused by some factors, such as physique factor, psychology, the teacher, environment, and facilities infrastructure. Efforts that can be made are monitoring by parents and giving rewards so that students' interest increases when learning to read. While in school, teachers can provide additional lesson hours and provide methods and media that can support reading skills.